The effect of membership in producer organizations on women's empowerment: Evidence from Kenya - Mwambi, M.; Bijman, J.; Galiè, Alessandra (Elsevier, 2021)
In developing countries, producer organizations (POs) are important for achieving women empowerment mainly through promoting women's access to the organization's resources and services. However, by improving access to markets and technologies, household membership in POs often results in commercialization of smallholder farming, leading to women disempowerment as men take over control of the farm. We use data from dairy smallholders in Kenya to explore the impact of membership in bargaining and processing POs on women empowerment. Applying the Women Empowerment Livestock Index, we capture six domains of empowerment: production; nutrition; resources; income; opportunities; and workload. We find that when a household joins any PO, regardless of whether the man or the woman in the household is the registered member, women achieve a higher control over production decisions, buying and selling of land and cows, use of loans and receiving dairy income. Distinguishing by gender of membership, there is stronger women empowerment when the woman in the household is a member. We also find that woman membership in bargaining POs results in greater empowerment, in terms of ownership of cows, than woman membership in processing POs. The paper suggests that women empowerment is affected by the functional characteristics of POs.